Eigenvalue criteria for semipositone Neumann elliptic problem in exterior domain. (October 2021) - Cianciaruso, Filomena; Pietramala, Paolamaria
Abstract: New criteria are established for the existence of positive solutions of a semipositone elliptic problem on the exterior of a ball in which the Neumann boundary conditions are non local. These criteria are determined by the relationship between the behaviour of the nonlinearity as the variable tends to 0 or ∞ and the principal (positive) eigenvalue of a suitable associate linear Hammerstein integral operator.